Pelatihan Perencanaan Karir bagi Siswa SMPN 1 Tamalatea Kabupaten Jeneponto: Career Planning Training for Students of SMPN 1 Tamalatea, Jeneponto Regency - Andi Fatmayanti; Rezeki Amaliah; Tri Susantri (ADPERTISI, 2022)
Career guidance works to provide understanding to students in planning work. However, during the implementation of brave learning due to the Covid-19 career guidance, it has never been implemented at SMPN 1 Tamalatea. The importance of career guidance for students is therefore held career planning training which is expected to be able to provide knowledge to students in planning the right career. Participants in this activity consisted of grade VIII & IX students. The method used in this PkM is through a complete presentation of the material which is then accompanied by a question and answer session with the participants. The results of the activity showed that this activity received a positive response from students and BK teachers. Data obtained that this PkM activity is beneficial, interesting, helps the implementation of the BK program, and needs to be re-implemented.